Research on Augmented Reality (AR) Intelligent Maintenance Guide System. Issue 1 (January 2021) - Sheng, Yi; Gu, Jiayan
Abstract: The augmented reality (AR) intelligent maintenance guide system is researched. To do the maintenance with high efficiency and low cost, AR technology is a solution. The system is to provide a guide system with interactive display of virtual and reality. The test results show that the system has the function of reading, scanning, communication. The system can combine the virtual and reality.